Flexible composite-nanofiber based piezo-triboelectric nanogenerators for wearable electronics. Issue 21 (17th May 2019) - Wu, Yinghong; Qu, Jingkui; Daoud, Walid A.; Wang, Lingyun; Qi, Tao
Abstract : A flexible BCZT/PVDF-HFP composite-nanofiber based PTNG is developed. The uniform distribution of BCZT nanoparticles on the fiber surface significantly enhances the electrical properties, where the highest output is achieved when BCZT is prepared via the sol–gel method. Abstract : With the rapid development of wearable electronics, flexible and sensitive energy harvesters have recently attracted considerable attention. Herein, a novel piezo-triboelectric nanogenerator (PTNG) based on BCZT/PVDF-HFP composite nanofibers (BP-based NFs) is fabricated using silicone rubber as the negative triboelectric counterpart. The introduction of BCZT nanoparticles markedly improves both the piezoelectric and triboelectric properties of the BP-SG PTNG, where the output voltage and current density are 2.5–3 fold higher than those of pure PVDF-HFP PTNG. Owing to the uniform distribution of BCZT particles on the fiber surface via electrospinning, the maximum power density of the device reaches 161.7 mW m −2, representing 5.5-fold improvement compared to that of BaTiO3 /PVDF-based composite PTNG. The device shows stable output for 1200 cycles and after three month storage and exhibits high sensitivity to minute body movements as proved by the output response in both two-electrode and single-electrode modes. This study demonstrates a novel approach to fabricate flexible PTNGs with simple structure and high sensitivity for use in self-powered wearable electronics.